The Effect of Organizational Commitment and Physical Work Environment on Turnover Intention with Job Satisfaction as an Intervening Variable at Company - Solikhah, Safa’atus; Andriani, Dewi (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to examine the Effect of Organizational Commitment and physical Work Environment on Turnover Intention With Job Satisfaction As an Intervening Variable. This study uses a quantitative approach with a survey method. The sampling technique used a saturated sample, that is, the total population was Sampled. So the sample used in this study amounted to 70 employees who work at PT. Setia Kawan Grup in Mojosari. The data analysis technique used Partial Least Square (PLS) with SmartPLS software. The results of study found that there was an influence between Organizational Commitment on Job Satisfaction at PT. Setia Kawan Grup, there is no effect of Organizational Commitment on Turnover Intention at PT. Setia Kawan Grup, there is an effect of the Physical Work Environment on Job Satisfaction at PT. Setia Kawan Grup, there is no effect of the Physical Work Environment on Turnover Intention at PT. Setia Kawan Grup, there is no effect of Job Satisfaction in Turnover Intention at PT. Seti Kawan Grup, there is an effect of Organizational Commitment on Turnover Intention with Job Satisfaction as an intervening variable at PT. Setia Kawan Grup, and there is no influence of the Physical Work Environment on Turnover Intention with Job Satisfaction as an intervening variable at PT. Setia Kawan Grup.